The Understanding of Muhammadiyah Preachers on the Problem of Drought in Gorontalo, Indonesia - Sri Rahayu Ayuba; Chaterina Puteri Doni; Suharia Sarif (Cakrawala: Jurnal Studi Islam, 2020)
Drought is one of the greatest disasters that will be experienced by humans at the end of time. The level of drought in the Limboto watershed is in the vulnerable category, so special handling is needed as an effort to mitigate this disaster. This study aims to (1) determine the Muhammadiyah propaganda model in the District of Bongomeme, Gorontalo Regency (2) determine the community's understanding of the Muhammadiyah propaganda in the District of Bongomeme, Gorontalo District. The use of mixed methods (qualitative and quantitative) forms the basis of this research. In the qualitative method, the data collection of da'wah models is done through observation, interviews and documentation. Whereas quantitative data is carried out through questionnaires. Based on the results of the study obtained a link between the high drought and the level of understanding and application of Islamic religious values ​​and preachers of Muhammadiyah. This is indicated by the value obtained on average 1.75, which means the level of public understanding is still in the bad category. As for the level of mastery of preaching material on drought, a similar value is obtained, which is 1.85, which means that very little material preaching by Muhammadiyah preachers contains about the drought.